From resistance to adoption: A mixed-methods framework for successful manufacturing execution system implementation in digital transformation initiatives - Sutra, Debi; Mansur, Agus (OPSI, 2025)
This study develops an optimized change-management framework to mitigate Manufacturing Execution System (MES) 3.0 implementation failure by integrating quantitative and qualitative findings from the ADKAR model through a socio-technical lens. Using explanatory sequential mixed-methods design, quantitative data from 248 respondents were analyzed via multiple and moderated regression, followed by in-depth interviews with 10 key stakeholders analyzed in NVivo. The phases were triangulated using a socio-technical framework to identify systemic patterns. Quantitatively, employee resistance significantly moderated the relationship between ADKAR components and implementation failure (β = 0.657, p = 0.040), with awareness (β = −0.778, p = 0.000) and knowledge (β = −0.168, p = 0.012) showing significant negative effects. Qualitative findings revealed five major themes: multidimensional resistance (active 15%, passive 35%, concealed 20%, neutral 30%), ADKAR implementation gaps, systemic contextual factors, and mitigation strategies. Triangulation exposed hierarchical cultural barriers, digital-literacy gaps, and insufficient reinforcement mechanisms. We propose an integrated hexagonal socio-technical model with six components and 24 sub-elements: Goals (4), People (4), Infrastructure (4), Technology (4), Culture (4), and Processes (4) for sustainable MES 3.0 implementation. This study contributes empirical evidence of resistance as a moderator and provides actionable guidance for digital transformation in manufacturing organizations.